Ethnomathematics of Ilabulo: Exploring Mathematical Concepts in Gorontalo’s Traditional Food - Damayanti, Taulia; Irfah, Auli (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
Mathematics is often perceived as abstract and disconnected from students’ daily lives, yet ethnomathematics highlights that mathematical ideas are embedded in cultural practices. This study explores the ethnomathematical concepts found in the preparation of Ilabulo, a traditional food of Gorontalo, Indonesia, through a qualitative ethnographic approach involving observation, documentation, and informal interviews with two local participants. The findings reveal two main concepts: ratio and proportion in mixing ingredients and geometry in wrapping and shaping, both of which were mapped to relevant school mathematics topics and further developed into contextual word problems. In addition, the study suggests that the process of preparing Ilabulo can be adapted into a video-based learning resource to support the problem-orientation stage in Problem Based Learning (PBL). These results demonstrate that everyday cultural practices can serve as meaningful contexts for mathematics learning, making abstract concepts more engaging and relevant while also strengthening students’ cultural identity.